№1 (а)
ответ: -\frac{4}{3}" class="latex-formula" id="TexFormula2" src="https://tex.z-dn.net/?f=x%20%3E%20-%5Cfrac%7B4%7D%7B3%7D" title="x > -\frac{4}{3}">
№1 (б)
№2 (а)
-4} \atop {x\leq -2.5}} \right." class="latex-formula" id="TexFormula6" src="https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx%3E-4%7D%20%5Catop%20%7Bx%5Cleq%20-2.5%7D%7D%20%5Cright." title="\left \{ {{x>-4} \atop {x\leq -2.5}} \right.">
№2(б)
\frac{36}{5}" class="latex-formula" id="TexFormula10" src="https://tex.z-dn.net/?f=x%20%3E%20%5Cfrac%7B36%7D%7B5%7D" title="x > \frac{36}{5}">
ответ: \frac{36}{5}" class="latex-formula" id="TexFormula12" src="https://tex.z-dn.net/?f=x%20%3E%20%5Cfrac%7B36%7D%7B5%7D" title="x > \frac{36}{5}">
б)ax-b+bx-a=a(x-1)-b(1-x)=a(x-1)+b(x-1)=(x-1)(a+b)
в)ax-y+x-ay=x(a+1)-y(1-a)=x(a+1)-y(a+1)=(a+1)(x-y)
Г)ax-2bx+ay-2by=a(x+y)-2b(x-y)=a(x+y)+2b(x+y)=(x+y)(a+2b)